2021
DOI: 10.3390/cancers13205067
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Pancreatic Cancer: Insight into Mechanisms

Abstract: The prevalence of obesity in adults and children has dramatically increased over the past decades. Obesity has been declared a chronic progressive disease and is a risk factor for a number of metabolic, inflammatory, and neoplastic diseases. There is clear epidemiologic and preclinical evidence that obesity is a risk factor for pancreatic cancer. Among various potential mechanisms linking obesity with pancreatic cancer, the adipose tissue and obesity-associated adipose tissue inflammation play a central role. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 230 publications
2
24
0
Order By: Relevance
“…In the case of diabetes‐specific risk factors, our 15.5% increase in pancreatic cancer risk per mmol/L increase in fasting plasma glucose in our participants with type 2 diabetes is identical to that found in a recent meta‐analysis 14 . Sustained basal hyperglycaemia is a likely surrogate for increased insulin resistance which can stimulate a range of tumour‐promoting molecular pathways 15 . Persistently high fasting blood glucose levels relative to the contemporaneous HbA 1c could thus represent a simple laboratory risk indicator.…”
Section: Discussionsupporting
confidence: 85%
“…In the case of diabetes‐specific risk factors, our 15.5% increase in pancreatic cancer risk per mmol/L increase in fasting plasma glucose in our participants with type 2 diabetes is identical to that found in a recent meta‐analysis 14 . Sustained basal hyperglycaemia is a likely surrogate for increased insulin resistance which can stimulate a range of tumour‐promoting molecular pathways 15 . Persistently high fasting blood glucose levels relative to the contemporaneous HbA 1c could thus represent a simple laboratory risk indicator.…”
Section: Discussionsupporting
confidence: 85%
“…Pancreatic ductal cancers are relatively uncommon, difficult to detect, and frequently diagnosed at an advanced stage with low survival rates due to reduced effective treatment options [185,186]. Chronic inflammation, attributable to obesity, diabetes, diet, and pancreatitis, usually precedes pancreatic cancers [187,188]. Extensive studies have focused on SphK/S1P/S1PR and insulin signalling in pancreatic beta cells due to their importance in inflammation, insulin resistance, and diabetes [189,190].…”
Section: S1p In Pancreatic Function and Cancermentioning
confidence: 99%
“…Obesity-associated adipose tissue inflammation may play a central role in the development of PC and the promotion of PC growth [ 32 ]. Chronic inflammation, hormonal effects, circulating adipokines, and adipocyte-mediated inflammatory and immunosuppressive microenvironments are involved in the association of obesity with PC [ 33 ].…”
Section: Patient Factors: Hyperglycemia and Obesitymentioning
confidence: 99%
“…Recently, Zorbas et al showed that obesity was significantly associated with higher risk of postoperative complications and mortality in patients with body mass index ≥ 40 after pancreatoduodenectomy [ 38 ]. Obesity-associated adipose tissue inflammation may play a central role in the development of PC and the promotion of PC growth [ 32 ]. Thus, anesthetics with the effect of inhibiting obesity-induced inflammation may improve postoperative outcomes [ 35 ].…”
Section: Perioperative Anesthesia Managementmentioning
confidence: 99%